The Significance of Foreign Direct Investment Registered Projects and Employment Creation in the Sectors of Ghana’s Economy - Yeboah, Evans; Agyei, Dacosta Boateng; Li, Ran; Sossoe, Anita; Tetteh, Mavis; Amankwa, Aisha (Asian Journal of Economics and Empirical Research, 2022)
The flow of foreign direct investment (FDI) into the Ghanaian economy has contributed significantly to the various sectors. This study seeks to assess the impact of registered investment (FDI and domestic) projects on employment generation in the agriculture, building & construction, manufacturing, and service sectors. The data for this study was obtained from the Ghana Investment Promotion Centre (GIPC) for the period 2001 to 2018. The Kwiatkowski-Phillips-Schmidt-Shin (KPSS) test showed a unit root existence in the time series. The regression results show no significant impact of registered investment projects on the agriculture and manufacturing sectors at a 5% significance level. Our findings also indicated that employment creation through registered investment projects has no effect on the manufacturing industry. The outcome also revealed that the service sector benefits more from FDI than the other sectors. It is recommended that the government boost these non-performing sectors with incentives to attract more investors.